Support for de public pension system under the behavioral paradigm - Cid Moreno, Daniel; Rodríguez-Iglesias, Isabel; Moreno-Adalid, Ana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The public pension system in Spain has been in a complicated situation for years. Institutions are questioning its sustainability in the medium and long term. Despite these warnings, no changes are being made to bring about an improvement. This article analyzes, from the perspective of behavioral economics, the biases and heuristics involved that are holding back change. In addition, behavioural proposals are put forward that would boost individual savings and could be the solution to the problem.